Avian abundance and reproductive success in the intermountain west: Local‐scale response to the conservation reserve program - W. Matthew Vander Haegen; Michael A. Schroeder; Wan‐Ying Chang; Shannon M. Knapp (Wildlife Society Bulletin)
ABSTRACT Conversion of extensive shrubsteppe communities to cropland has greatly reduced the habitat available to grassland‐ and sagebrush‐obligate birds in the Intermountain West of the United States. In Washington State, approximately 600,000 ha of converted farmland have been planted to perennial grasses, forbs, and shrubs under the Conservation Reserve Program (CRP), currently the largest‐scale effort creating perennial grassland habitat in this region. From 2003 to 2005 we sampled breeding birds and vegetation characteristics on 48 study sites in CRP and in native shrubsteppe. We used generalized linear models to examine characteristics associated with avian abundance and reproductive success. Abundance of shrubland and grassland birds was more closely associated with site vegetation than either management (planting of native vs. exotic grasses) or landscape factors, with cover of shrubs the dominant variable both for shrubland (positive effect) and for grassland (negative effect) birds. Daily survival rate of 1,377 nests in CRP was equal to or greater than that for nests in shrubsteppe and was similar for CRP planted with native versus exotic grasses. Seasonal reproductive success (young/breeding pair) of 2 focal species—Brewer's sparrow (Spizella breweri; n = 81pairs) and Savannah sparrow (Passerculus sandwichensis; n = 58)—also was similar between CRP and native shrubsteppe. The CRP has the potential to significantly increase habitat available to shrubland and grassland birds in the Intermountain West and to increase local populations. Because shrubs take significantly longer than herbaceous plants to achieve a size beneficial to birds, CRP grasslands with a well‐developed sagebrush (Artemisia spp.) component should be viewed as a long‐term investment. © 2015 The Wildlife Society.